Benzo- and Naphthopentalenes: Syntheses, Structures, and Properties - Kato, Shin-ichiro; Kuwako, Satoshi; Takahashi, Nobutaka; Kijima, Tomokazu; Nakamura, Yosuke (Journal of organic chemistry, 2016)
Benzo- and naphthopentalene derivatives were synthesized, and the effects of structural variations on their antiaromaticity and optoelectronic and electrochemical properties were examined experimentally and theoretically in detail. The results unveiled that with increasing the bond order of the carbon–carbon bond ([5,6] junction) shared by the pentalene and aromatic moieties, the 8π antiaromatic character of pentalene is enhanced and the HOMO–LUMO gap is decreased, which accompanies both the elevation of the HOMO level and the lowering of the LUMO level. The ethynylene units between the pentalene skeleton and the phenyl groups proved to extend π-conjugation sufficiently.